A horse race of alternative monetary policy regimes under bounded rationality - Joel Wagner; Tudor Schlanger; Yang Zhang (Bank of Canada, 2022)
We introduce bounded rationality, along the lines of Gabaix (2020), in a canonical New Keynesian model calibrated to match Canadian macroeconomic data since Canada's adoption of inflation targeting. We use the model to provide a quantitative assessment of the macroeconomic impact of flexible inflation targeting and some alternative monetary policy regimes. These alternative monetary policy regimes are average-inflation targeting, price-level targeting and nominal gross domestic product level targeting. We consider these regimes' performance with and without an effective lower bound constraint. Our results suggest that the performance of history-dependent frameworks is sensitive to departures from rational expectations. The benefits of adopting history-dependent frameworks over flexible inflation targeting gradually diminish with a greater degree of bounded rationality. This finding is in line with laboratory experiments that show flexible inflation targeting remains a robust framework to stabilize macroeconomic fluctuations
Keywords: E; E2; E27; E3; E4; E5; E52; E58; 330; Central bank research; Economic models; Monetary policy framework; Monetary policy transmission